Comparison study of Fibonacci code algorithm and Even-Rodeh algorithm for data compression - Rachmawati, D; Budiman, M A; Subada, M A (Journal of physics. Conference series, 2019)
The need for greater storage capacity is the cause of various compression techniques. By compressing, large data will be reduced in size to save storage capacity. This research will use Even-Rodeh code algorithm and Fibonacci code algorithm to compress the data. The performance of algorithms will be measured by Bitrate, Compression Ratio, Space Saving, and Compression Time (millisecond) and Time Decompression (millisecond). Compression is done by reading String in the text file, then Even-Rodeh Code algorithm and Fibonacci code algorithm create String code and perform compression process. The result of compression is the file with extension *. C and *. Fib which contains character information and String Bit. The results of compression can be decompressed to the original text file. The system test used a sample of Strings consisting of one type of character (Homogen String) and String comprising more than one kind of character (Heterogenous String) is stored in the text file by extension * .doc, * .docx, * .pdf. From the compression process on the homogenous String, the Fibonacci code algorithm is more efficient about the compression ratio of 0.25 and decompression time is 0.011 milliseconds compared with the Even-Rodeh code algorithm. While in the compression process on heterogeneous String Fibonacci Code algorithm is better than the Even-Rodeh code algorithm with an average Compression Ratio of 0.65 and decompression time faster with an average of 0.293 milliseconds.